DEEP LEARNING ALGORITHMS FOR COVID-19 DATA ANALYTICS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
COVID-19 is a viral disease that affects humans very fastly where the death rate also increases day by day. Recently a vaccine for COVID-19 is identified and being used by a particular age of people. There are different types of tests being used to identify whether a person is having a corona or not. Mainly, the lung is being affected by people and unable to breath continuously. For diagnosing lunge related problems, Chest X-ray and chest CT imaging techniques are widely used. Various researches are being conducted to identify corona virus by using chest X-ray images. Still, a substantial chest x-ray is a lower cost process in comparison to chest CT. Deep Learning techniques are being applied for analyzing a large amount of chest x-ray images which could screen the COVID-19.This paper analyzes the various deep learning techniques applied for identifying coronavirus symptoms using chest x ray images. Convolutional Neural Network (CNN) algorithm has achieved 95% accuracy for analyzing COVID 19 and Normal patients.